Literature Study: Integration of Ethnomathematics in Mathematics Learning in Schools - Simbolon, Ronti (JMEA : Journal of Mathematics Education and Application, 2024)
Ethnomathematics is a mathematics learning approach that integrates local culture into the learning process. This method aims to increase students' relevance and understanding of mathematical concepts through the cultural context they are familiar with. This study uses the literature study method to explore various studies that examine the implementation of ethnomathematics in mathematics learning in schools. Research shows that the integration of ethnomathematics can increase learning motivation, understanding of concepts, mathematical abilities in problem solving, and appreciation of local culture. Implementing ethnomathematics in mathematics learning involves developing teaching materials that combine local cultural elements, teacher training, and curriculum adjustments. Various studies show that this approach is effective in improving student learning outcomes, especially in areas with diverse cultural riches. However, there are challenges in implementing ethnomathematics, such as lack of resources, limited teacher knowledge of local culture, and resistance to curriculum change. To overcome these challenges, cooperation between government, educational institutions and local communities is needed. This study also highlights the importance of further research to measure the long-term impact of the integration of ethnomathematics in mathematics learning. Thus, ethnomathematics can not only improve the quality of mathematics learning, but can also contribute to the preservation of local culture.